2011
DOI: 10.1071/zo10047
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tooth-supporting bone in the koala (Phascolarctos cinereus) with age

Abstract: This study investigated changes in alveolar bone height in free-ranging koalas of different age groups. Twenty-seven free-ranging Queensland koalas (15 female, 12 male), admitted to the Moggill Koala Hospital, Brisbane, were used in this study. Koalas were divided into three groups (young, adult, old) on the basis of tooth wear, each group containing nine animals. Defleshed jaws were examined for the presence of alveolar bone defects. The distance from the cemento-enamel junction and the interproximal crestal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Gingivitis and periodontitis was reported in koalas (Bird, 2002) some with severe loss of alveolar bone associated with age and conditions such as food impaction and tooth movement (Lee et al, 2011). The areas found most susceptible to interproximal alveolar bone loss were those adjacent to the second and third molars (Figure 2-13), in both the maxilla and mandible.…”
Section: Oral Disease In the Koalamentioning
confidence: 99%
See 3 more Smart Citations
“…Gingivitis and periodontitis was reported in koalas (Bird, 2002) some with severe loss of alveolar bone associated with age and conditions such as food impaction and tooth movement (Lee et al, 2011). The areas found most susceptible to interproximal alveolar bone loss were those adjacent to the second and third molars (Figure 2-13), in both the maxilla and mandible.…”
Section: Oral Disease In the Koalamentioning
confidence: 99%
“…In dogs and cats when controlling for age the oral health index still increased in one study (Gawor et al, 2006). In the koala advanced tooth wear occurs in older animals, natural abrasion and attrition reduces the stability of the teeth which increases the risk of having bone loss (Lee et al, 2011). Sexual dimorphism occurs in many aspects of dentistry.…”
Section: Age and Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many studies determining which of the causative agent(s) initiate oral diseases in humans and domesticated animals. Marsupials also have oral diseases 3,4 and culture-dependent studies have shown a range of bacteria can be isolated from the marsupial oral cavity 5 . However culture-based studies, while useful to enable precise characterisation of putative periodontopathogens, generally underestimate microbial community diversity.…”
mentioning
confidence: 99%